Archaeometric approach to identifying the provenance of white marbles from the shipwreck of Cala Cicala (Crotone, Calabria, Italy). (April 2020) - Antonelli, Fabrizio; Bloise, Andrea; Bruno, Fabio; De Luca, Raffaella; Allegretta, Ignazio; Medaglia, Salvatore; Taliano Grasso, Armando; Terzano, Roberto; Miriello, Domenico
Highlights: White marbles from the shipwreck of the Cala Cicala (Calabria, Italy) were analyzed. The provenance of the white marble samples was determined. Information about the trade routes in the Roman imperial age was provided. Abstract: This paper presents the results of an archaeometric study performed on white marbles from the shipwreck of Cala Cicala (Crotone, Calabria, Italy). The stone materials, especially the white marbles, are an excellent tool for reconstructing the trade routes of the past and studying the relationships between ancient populations. The purposes of this study were to establish the provenance of the white marbles of the shipwreck of Cala Cicala (Crotone, Calabria, Southern Italy) and to use analysis of their composition to acquire more knowledge about trade routes in the Roman imperial age. The 35 samples of white marble were studied by X-ray diffraction (XRPD), optical microscopy (OM), and isotopic analysis (δ 13 C and δ 18 O). All of the archaeometric data collected indicate that the marble blocks in the cargos are from the Greek island of Thasos, in the northern Aegean Sea.